DEVELOPMENT OF FINANCIAL PERFORMANCE MEASUREMENT BASED ON THE CONCEPT OF ALL INCLUSIVE INCOME IN ENTITIES LISTED IN INDONESIA STOCK EXCHANGE (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Change of historical value-based accounting principles to fair value-based accounting, resulting in the emergence of an “Other Comprehensive Income or OCI” account. The concept of recognizing all inclusive income, which is used by IFRS and Indonesian SAK, is the basis for presenting other comprehensive income in the income statement. This format change has led to the idea of ​​developing a financial performance measurement (ROA comprehensive income version and ROA net income version with profits attributable to parent and non-controlling owners).